The Process of Translating Process and Reality (Nóema, 2020)
In translating Process and Reality it is important to bear in mind that Whitehead’s magnum opus has a metaphysical, cosmological and systematic nature. Whitehead’s system is an open one; its categories are interrelated and should not be considered apart from the wholeness of the metaphysical system. Metaphysical generalities are hard to express and our language is greatly limited. Notwithstanding, the translator of Process and Reality needs to seize exact and rigorous words in order to achieve the true “linguistic revolution” introduced by Whitehead in Process and Reality. The bilingual Italian translation of PR is an outstanding achievement that was carried out by Maria Regina Brioschi.
Keywords: Translation; Process; Generalization; Language; Metaphysics